Sources of strength: a process evaluation of a university-high school partnership to promote mental health protective factors - Biber, Duke; Brandenburg, Gina (Frontiers in Public Health, 2024)
The purpose of this manuscript was to discuss the implementation process of a student-led positive psychological and behavioral program (i.e., Sources of Strength) at a local high school to prevent opioid use and suicide behavior. Over the course of 2 years of programming, university undergraduate students worked alongside and mentored high school students to implement school-wide and focused campaigns that targeted each of the domains of the Sources of Strength wheel (i.e., mental health, family support, positive friends, mentors, healthy activities, generosity, spirituality, and medical access). The summed total student reach for 2 years of implementation was 8,682 students. The average participation was 456.95 students per campaign. The average percentage of the school population that engaged in each campaign was 34.7%. While no outcome opioid use or suicide behavior data were collected, the participation in the programming was high. Universities can continue to engage with local high schools to provide support, collaboration, and mentorship to promote positive and supportive school culture. Using university undergraduate students to serve as leaders can provide them with applied learning opportunities, mentorship for high school students, and reduce the expectancy for high school staff to establish the program on their own.